PROSES MORFOLOGIS ISTILAH-ISTILAH DALAM TAJEN - Komang Putri Yadnya Diari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Balinese language has really rich lexicon / vocabularies packaged in a frame of bothtraditional culture and religion. One of the cultural activities which is interesting to be studiedfrom linguistic point of view is tabuh rah or tajen (traditional cockfighting) which own uniquevocabularies with its specific characteristics that cannot be understood by societies. The termsused in this tradition are property of Balinese language that need to be comprehended both fromits own root word and the words that have undergone morphological process. Morphologicalprocess basically is a word formation process from its root word and the addition of affixation,repetition and reduplication, and pluralisation (Ramlan, 1983:5). Research method used in thisstudy is descriptive qualitative by using interview technique to obtain the data about thevocabularies in this tradition from the informants. This research was also supported by anothertechnique such as note-taking to ease the research process, particulaly to remember the obtaineddata, and recording technique to record the result of interview from the informantsKeywords: Morphology, Terms, Tajen